'Do you come from a land down under?' Characteristics of the international trade in Australian endemic parrots. (March 2017) - Vall-llosera, Miquel; Cassey, Phillip
Abstract: The wildlife pet trade is a billion dollar transnational business that has devastating effects on global biodiversity. Australian parrots are highly sought by overseas collectors due to their uniqueness, however, the characteristics of this demand are poorly understood. We used trade reports to the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Trade Database to analyse spatial and temporal trends in live commercial trade of Australian endemic parrots. We also investigated whether the volume of trade is influenced by variables related to species availability and popularity in Australia, and ease of captive breeding. We collected information on over 20, 000 transactions for the period 1975–2014. Between the years 2000 and 2005 the volume of trade sharply declined, possibly due to the effect of international bird trade bans as a response to the avian influenza crisis. Australia has a minimal role in the trade of its own endemic parrots, even before the passing of the Australian Environmental Protection and Biodiversity Conservation (EPBC) Act 1999 that banned the export of native wildlife. Key international exporters are Netherlands (25.8% of all exports) and Belgium (17.5%), and captive breeding is the major source. The USA (7.5% of all imports) and Japan (7.3%) are key importers, and Netherlands, USA and South Africa are also major intermediaries. Species that have larger Australian distributions, and species abundant in Australian private and public captivity, are traded internationally in higher volumes. International trade in Australian endemic parrots is an example of an exotic pet market that is sustainably supplied by overseas captive breeding, while native populations are effectively protected by genuine national trade bans. Highlights: Australia is only the eighth main exporter of Australian endemic parrots. Most volume of trade are captive bred birds sourced from Netherlands and Belgium. Volume of trade showed a steady increase except for period between 2000 and 2005. Overseas captive breeding could be a sustainable source for exotic bird trade.